IMPLEMENTASI KEBIJAKAN TENTANG PELAYANAN PERSAMPAHAN / KEBERSIHAN KABUPATEN SIDENRENG RAPPANG - Hadriani Dahri; Erfina Erfina; Monalisa Ibrahim (JIA: Jurnal Ilmiah Administrasi, 2022)
The purpose of this study was to determine the implementation of the policy of Regional Regulation number 12 of 2011 Article 9 regarding waste services / environmental cleanliness and the factors that influence the implementation of policies in the Village of Rappang, Panca Rijang District, Sidenreng Rappang Regency. The population in this study was 6,182 residents in Rappang Village with sampling using the slovin formula so that a sample of 98 people was obtained based on non-probability sampling technique. This type of research is observation and questionnaire. The data analysis technique used is frequency table analysis and data quality test with the help of the IBM SPSS Statistics 22 program. The results of this study are the implementation of Regional Regulation number 12 of 2011 article 9 regarding waste services / environmental hygiene in Rappang Village, Panca Rijang District, Sidenreng Rappang Regency based on the results of the recapitulation of policy implementation variables in the good category with a percentage of 67%. The factors that influence the implementation of the policy of Regional Regulation number 12 of 2011 are disposition factors that influence 27.9%, bureaucratic structure factors influence 27.3%, communication factors affect 22.5% and resource factors influence 20.8% .